Heyrath macht Friede: Oder/ Der erkannte Tuisco - Heidenreich, David Elias,Friedrich,Magdalena Sibylle,Salfeld, Christoph (Salfeld, 1669)
Deutsche Drucke zur Festkultur des Barock (1601-1700)
Verf. ermittelt
Keywords: Quelle; CD-ROM; Libretto; Festbeschreibung